Pemanfaatan Teknologi Biopori untuk Pembuangan Sampah Organik dan Pencegahan Banjir di Kelurahan Menteng Atas - Adidarma, Wijaya; Susanto, Tri; Surya Irawan, Diki (Indonesian Journal for Social Responsibility, 2019)
Floods that hit parts of Jakarta today, due to human negligence in paying attention to the environment. Human activities by building buildings or other facilities without taking into account the open land area causes the rainwater catchment area to decrease. Likewise also the disposal of garbage in rivers or gutters that are not in place, so that water can not flow smoothly, which in turn results in an overflow of water. Therefore, it takes the making of biopori infiltration holes (LRB), where the main ingredient is organic waste. The LRB functions to absorb water into the soil and organic waste planted in holes can be used to make compost. LRB does not require a large area, and the manufacturing process is straightforward, this is undoubtedly the right solution for areas with narrow open land. However, this appropriate technology must be accompanied by community care to want to sort waste and treat LRB. Community care to preserve nature is the primary key to flood prevention.